Analysis of Socio-Economic Factors Affecting Waste Management (Case Study of Mandau District, Bengkalis) - Meuthia Pangerani; Yusni Ikhwan Siregar; Ridwan Manda Putra (Berkala Perikanan Terubuk, 2023)
In recent years, the waste problem that has occurred in Indonesia has increased, including in Mandau District. One of the problems that occurred in Mandau District was the accumulation of waste due to the unavailability of temporary disposal sites around the community's residential areas, causing the community to dispose of waste indiscriminately. This study aims to determine the socio-economic factors that influence waste management in Mandau District. Obtaining data in this study is by direct observation in the field and in-depth interviews with stakeholders involved in waste management in Mandau. The results of the study show that the social factors that influence waste management in Mandau District are influenced by human resources who are less supportive of waste management. There needs to be a contribution from the community and the private sector, the majority of the local community's last education is high school, there are no training programs provided to the community, there are no conflicts that occur around the TPA and Pemda regulations and policies that are quite effective in waste management. While the economic factors that affect waste management in Mandau include: local government budgets for waste management, incentives for waste workers and businesses obtained from waste management.